Pengaruh Budaya Terhadap Dinamika Bisnis Internasional - Tan Wan I; Hendra Dewantara; Rahmadhanti Rahmadhanti; Yandi Suprapto (STIE AMKOP, 2023)
With data exposure and analysis, the background will lead to case studies of international business marketing with an eye on that culture. The author will also explain how cultural elements can be so important in International Business. The method used in this study is to process data and collect data. In collecting study data, this was obtained from online journals depending on the topic of discussion. In simple terms, cultural influences are very crucial because this allows them to be great successes or total failures. Loss is not from business, loss is part of life. If other researchers only mostly do theoretical research, then it cannot fully assess the performance of a company. In this case, P&G has been very competent in showing its professional side. P&G is able to dominate the global market as an international business system. In terms of marketing capabilities, understanding and recognition of cultural aspects can be said to be very good because P&G is always responsible for the results. Keywords: Business, International, Cultural.